Trouble at school: a systematic review to explore the association between childhood bullying and paranoid thinking. Issue 3 (3rd July 2017) - Jack, Alexander H.; Egan, Vincent
Abstract: Background: Bullying is prevalent, and is a risk factor for the development of psychotic phenomena. Distinct aetiologies exist for specific psychotic experiences; childhood bullying begets paranoid thinking. Objectives: To systematically review the literature that concerns the association between childhood bullying and paranoid thinking. Data Sources: Systematic searches were conducted using the PsycINFO, EMBASE, Medline, Web of Science and ProQuest databases, using derivations of paranoid thinking, bullying and childhood. A search of relevant reference lists was also conducted. Study Selection: In total, 2866 studies were found. After duplicates were removed, 1724 studies were screened by title and abstract. Resultantly, 79 studies were quality assessed. Of these, 11 were included in the qualitative data synthesis. Data Synthesis: All but one of the studies identified a positive association between the variables of interest, either as a co-occurring experience, or precipitant. Limitations: The included studies had methodological weaknesses, for example: inconsistent measurement of bullying and paranoid thinking, and the use of self-report measures; causality was difficult to determine. Conclusions: There is a positive association between childhood bullying and paranoid thinking. This finding adds to the evidence that specific psychotic phenomena have distinct developmental trajectories, though well-designed prospective studies are required to determine causality.